Anthropologists and participatory research in research for development projects: case studies from Ethiopia, Ghana and Burkina Faso [Abstract only] - Debevec, Liza; Salzer, A.K. (2014)
As anthropologists working in research for development (R4D) we are under pressure to use participatory methods in our research. However, the level and quality of participation often vary from one project to another or even within a single project, due to the type of participatory approaches used and due to differing perceptions by researchers and other stakeholders of what participation is all about. In this paper we examine the good and the bad of participatory approaches in R4D, by comparing methods (3D participatory mapping, Companion Modelling, Innovation platforms and other forms of participatory workshops) in concrete examples from R4D projects in 3 African countries (Ethiopia, Ghana and Burkina Faso). While participation is believed to offer an alternative to top-down decision making, it can, in some cases actually reinforce such decision-making processes and power differences. Understanding the potential of participation requires first an understanding of the political and social realities underlying the context in which it is being implemented.